Simulating rate- and temperature-dependent behaviors of adhesives using a nonlinear viscoelastic model. (August 2020) - Shim, Wonbo; Jang, Jinhyeok; Choi, Jae-Hyuk; Cho, Jeong-Min; Yoon, Sang-Jae; Choi, Chi-Hoon; Yu, Woong-Ryeol
Highlights: 3D Implementation method of Schapery's nonlinear viscoelastic model is proposed. Strain rate and temperature dependent failure criteria are formulated using the shift factor. Failure strength of adhesive at different rates and temperatures is predicted. The current approach is validated using lap shear tests at various strain rate and temperature. Abstract: Predicting the mechanical behavior of adhesives is important, because adhesives strongly influence the strength and reliability of adhesive–adherend structures. Herein, we report a simulation of the mechanical behavior of an adhesive, including its failure strength, using Schapery's nonlinear viscoelastic model. A detailed derivation of the nonlinear viscoelastic model for 3D implementation in finite-element software is presented. Experimental procedures for obtaining the model parameters from dynamic mechanical testing of lap-joint specimens are detailed. Strain-rate dependent failure criterion was employed using the shift factor and experimental lap shear tests at different strain rates to calculate the failure strain at different temperature. Then, the mechanical behavior of the adhesive in the adhesive joint at different rates and temperatures until its failure was simulated and compared with experiments, demonstrating the validity of the current approach.